Idiopathic Short Stature - A Case Report - Begum, Suraiya; Biswas, Dhiraj Chandra (Bangladesh Journal of Child Health, 2023)
Short stature in childhood is the most common reason for referral to pediatric endocrinologists. Idiopathic short stature is defined as ³2 SD below the corresponding mean height for a given age, sex, and population in a child with a normal birth size and normal body proportions and without evidence of any systemic, endocrine, nutritional, or chromosomal abnormalities. ISS children have normal GH responses to stimulation test and GH therapy has approved for the treatment of children with ISS. A six-year-old girl presented with not growing well in comparison to other peers since 6 months of her age. Her WAZ was -4.5 SD, HAZ was -7.7 SD, and projected height is far below parental target height. Bone age was 2-3 year and growth hormone stimulation showed normal growth hormone secretion. Here we reported a six-yearold girl diagnosed as a case of non-familial ISS and treated with growth hormone. Diagnosis of Idiopathic short stature was done by exclusion of other causes of short stature and growth hormone therapy was indicated. BANGLADESH J CHILD HEALTH 2022; VOL 46 (1) : 28-29